Identification of highly expressed, soluble proteins using an improved, high-throughput pooled ORF expression technology - Timothy Waybright; William K. Gillette; Dominic Esposito; Robert M. Stephens; David A. Lucas; James L. Hartley; Timothy D. Veenstra (BioTechniques)
This article describes an improved pooled open reading frame (ORF) expression technology (POET) that uses recombinational cloning and solution-based tandem mass spectrometry (MS/MS) to identify ORFs that yield high levels of soluble, purified protein when expressed in Escherichia coli. Using this method, three identical pools of 512 human ORFs were subcloned, purified, and transfected into three separate E. coli cultures. After bulk expression and purification, the proteins from the three separate pools were digested into tryptic peptides. Each of these samples was subsequently analyzed in triplicate using reversed-phase high-performance liquid chromatography (LC) coupled directly online with MS/MS. The abundance of each protein was determined by calculating the average exponentially modified protein abundance index (emPAI) of each protein across the three protein pools. Human proteins that consistently gave high emPAI values were subjected to small-scale expression and purification. These clones showed high levels of expression of soluble protein. Conversely, proteins that were not observed by LC-MS/MS did not show any detectable soluble expression in small-scale validation studies. Using this improved POET method allows the expression characteristics of hundreds of proteins to be quickly determined in a single experiment.